"I'm on a Rollercoaster": Women's Social Construction of Time. Issue 1 (1st January 2020) - Burnett, Ann; DiTunnariello, Nancy; DeGreeff, Becky L.
ABSTRACT: This study examines how women communicate perceptions of their socially constructed busy lifestyles. Qualitative interview results revealed six themes: 1) busyness is normal; 2) busyness is respected; 3) busyness is voluntary; 4) busyness is not voluntary; 5) busyness is viewed differently by men; and 6) busyness and the value of time. Through varied communication about time, women construct their busy lifestyle and actively live it. The study reveals challenges in the way "women's time" is negotiated in a busy life that primarily revolves around masculine time.